The Upadacitinib - New Janus Kinase Inhibitor - Literature Review - Michalina Grzelka; Jakub Plizga; Agnieszka Głuszczyk; Aleksandra Makłowicz; Ewelina Kopczyńska; Angelika Szpulak; Agata Frańczuk; Julia Głoskowska; Katarzyna Kuleta; Patrycja Karkos (Nicolaus Copernicus University in Toruń, 2024)
Atopic dermatitis (AD) is a chronic, recurrent dermatosis that affects an increasing percentage of the population. It usually affects children and resolves spontaneously, however, symptoms can persist into adulthood and even appear de novo later in life. The skin lesions that appear in this disease significantly reduce patients quality of life. Visual skin symptoms are exacerbated during stress, and pruritus leads to sleep problems. The effect of an inadequately controlled disease can even be a reduction in social activities and a reluctance to leave the house. The basis of treatment is skin care using emollients and avoiding triggers and aggravating factors. In the next stage, the doctor may prescribe topical or systemic treatment for the patient, depending on the severity of the disease. Such measures may not be enough, so more and more new drugs are being registered for the treatment of atopic dermatitis. One of them is upadacitinib, which appears to be extremely effective compared to other medications used to treat moderate to severe ad. It is a selective JAK inhibitor that reduces the inflammatory response by inhibiting migration, proliferation and cytokine secretion by granulocytes. It brings rapid and sustained effects in reducing skin lesions and reducing one of the most bothersome symptoms, pruritus.It may serve as a good alternative to the existing methods for treating moderate to severe atopic dermatitis The purpose of our study is to describe this new drug, its mechanism of action and discuss its possible benefits versus side effects.